PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Kiki Jasija; Fista Anaba Fitriana; Usman Aripin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this study is no other to know the extent to which the RME approach can improve the mathematical communication skills of students MTS Negeri 2 Purwakarta. The method used is quasi experiment with pretest-posttest nonequivalent control group design. The 5th grade students of MTsN 2 Purwakarta, which were 5 classes, were used as the population for this study while the research samples were class VIIA as the experimental class and VIIE as the control class. Determination of the sample is taken by the researcher accepting the state of the subject as it is after being grouped not randomly purely to be subjected to the treatment of mathematics learning through Realistic Mathematics Education approach and conventional approach. Instrument of research in the form of test instrument of mathematical communication ability. The results show that the improvement of students' mathematical communication ability using RME approach is better than using the usual approach.b